Stress, stress responses and coping strategies among bachelor nursing students - Pun, Khagi Maya; Samson, Priscilla; Timalsina, Rekha (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Inability to use effective coping strategies to minimize stress due to high academic and clinical expectations may affect nursing students’ health, academic and clinical performance. The aim of this study was to assess the level of stress, stress responses and use of coping strategies among bachelor nursing students. Methods: This-cross-sectional study included bachelor nursing program students selected by stratified random sampling technique from four nursing colleges affiliated to Tribhuvan University in Kathmandu Valley, Nepal, during August 18th to September 15th 2017. Data were collected using structured self-administered questionnaire. Perceived stress scale, physio-psycho-social responses scale and coping check lists were used to assess stress, stress responses and coping strategies of bachelor nursing students. Results: There were total 284 participating nursing students, 240 (84.5%) had moderate level of stress and 20 (7%) high level of stress. The common source of stress were assignments and workload (2.37±0.63), and clinical environment (2.16±0.74). Students’ physio-psycho-social responses during stress, 109 (38.4%) reported best emotional health, 125 (44%) best social behavioral and 189 (66.7%) best physical health. Coping strategies were, problem focused 175 (61.6%), social support coping 173 (60.9%), and avoidance coping 165 (58.1%). There was a positive correlation between stress and coping (r=0.138). Conclusions: More than 3/4th of bachelor nursing studentsreported moderate level of stress, problem focused coping strategies was commonly used and half of the students maintained good level of physio-psychosocial health during stress.